Capital–Labour and State Dynamics in Export Horticulture in North‐east Brazil. Issue 5 (12th September 2014) - Selwyn, Ben; Chhachhi, Amrita
ABSTRACT This article argues for the primacy of class relations and struggles as determinants of developmental processes and outcomes, emphasizing the evolving, dialectical nature of these relations. It does so by providing a case study of export horticulture in North‐east Brazil. It documents how the region's rural trade union has been able, through mobilizing its membership base, to achieve significant improvements in their livelihoods, pay and conditions. It also shows how the region's employers have responded to these gains by restructuring the labour force in order to attempt to fragment and weaken it. The article pays particular attention to the gender dynamics of class relations.